Quality analysis of shidal - a traditional fermented fish product of Assam, North-East India - Ahmed, S; Dora, Krushna Chandra; Sarkar, S.; Chowdhury, S.; Ganguly, S. (Indian Journal of Fisheries, 2013)
In the present study, proximate composition and bacteriological analyses of the fermented fish product, locally known as shidal, sampled from producers as well as retailers in eight different districts of Assam, were carried out. In proximate principle analysis, lower level of protein and fat content in the products obtained from retailers indicated the relative nutrient losses occurring at different stages of marketing chain. High total volatile base nitrogen (TVB-N), peroxide values and moisture along with promising microbial load in the retailer’s samples reflected poor quality, whereas those obtained in producer’s samples were within the acceptable limit. None of the samples revealed presence of the coliform bacteria, Escherichia coli and Salmonella sp. Yeast and fungal colonies were detected in the samples.